OVERVIEW MAKRO PADA SEKTOR PERBANKAN: TINJAUAN ASPEK KEPERILAKUAN DALAM MEWUJUDKAN GOOD CORPORATE GOVERNANCE - tjahjono, heru kurnianto (Jurnal Ekonomi & Studi Pembangunan, 2019)
The discuccion of this article is started from a macro overview of Indonesian economics related to banking sector. The failure therapies that had done to the financial crisis become a reason for the Indonesian government to utilitize another approach. Which is behavior in an organization. The effort to bring good corporate governance into reality become a new a realization that macro economics approach need to be followed by behavior aspect. The writer as a person who has knowledge of behavior science tries to elaborate macro economics policies in bankng sector related to its behavior aspect.